Salvaging the EU: Two-speed or dual-track reform? - Omar Alaeddin; Moutaz Abojeib; Wajahat Azmi; Mhd Osama Alchaar; Kinan Salim (Contemporary Economics, 2019)
In the most recent decade, the European Union has shown itself to be less robust than globalists imagined. Globalists believed that supranationality was weatherproof - that it would always outperform national alternatives and would survive adversity. Economic stagnation and Brexit belied these expectations. This essay investigates one aspect of the EU's supranational plight: incompatible goals and the difficulty of mutual accommodation, especially during hard times. EU supranationalists contend that the shared dreams assure harmonious results, but experience reveals that supranational government is shakier than advocates claim because shared ideals and benefits have not been enough for members to put aside conflicting national interests. These rivalries do not doom the European Union's globalizing project, but they do expose the vulnerabilities of its premises. Supranational union is proving to be unsatisfactory to both many centralizers demanding 'more Europe' and decentralizers insisting on 'less Europe'. EU leaders are aware of the problem but are wedded to a one-track, two-speed supranational approach that is destined to fail. A dual-track supranational solution analogous to China's 'one country, two systems' offers a better alternative.
Keywords: E02; E52; E61; F36; H63; H77; O52; P11; P17; 330; European Union; Reform; Dual-Track